Studi Pemberian Pupuk Organik dan Tinggi Genangan Air Terhadap Hasil Tanaman Padi Varietas Cigeulis Di Subak Sembung Kota Denpasar - JUNIADA, I GUSTI NGURAH DJORDI; DHARMA, I PUTU; WIRAATMAJA, I WAYAN (Agrotrop : Journal on Agriculture Science; Vol 7 No 2 (2017), 2018)
Study of Organic Fertilizer Providing High and Puddle of Results for Rice Varieties Cigeulis in Subak Sembung Denpasar City. Rice (Oryza sativa L.) is the staple vital food of Indonesian people. National rice production has not been able to meet the needs of the population, despite many efforts such as the use of improved varieties, fertilization, the use of agricultural machinery, and the use of pesticides. This study aimed to determine the effect of water level and organic fertilizers on crop yields of rice. This experiment used randomized block design in a factor groups, namely the combination of the water level and the dose of organic fertilizer. This research using analysis of variance (ANOVA) to determine the effect of treatment of the variables tested. If treatment significantly it will be followed by LSD test 5%. The results showed that the treatment is a combination of water level and organic fertilizers provide a very real effect on the growth and yield of rice (dry grain harvest/ha). Harvest dry grain yield per hectare obtained at the highest AMP2 treatment, namely without flooding water and organic fertilizers and 6 ton / ha at 10,78 ton / ha were significantly higher 33,78 % compared to the treatment of farmers ie 8,07 ton / ha (AGP0), but not significantly different from AMP1. Based on the research results, it can be recommended the application of water-saving cultivation of organic fertilizer with a dose of 4 tons / ha needs to be done to improve rice yields.